Konceptualni okvir sonaravne mobilnostne strukturacije v razmerah nadnacionalnega povezovanja - Hočevar, Marjan (Teorija in praksa, 2017)
The structural dynamics of social mobility is an important indicator for explaining social changes. Spatial mobility as an element of social mobility has a weak presence in sociology. In this paper, we argue in favour of an integrated examination of mobility. We analyse the discord between the rigid temporal-spatial organisation of a national society and the processes of deterritorialisation and supranational integration. We demonstrate why mobility has become a central feature of sustainable social inclusion, especially with the involvement of actors in the extended relational modalities in the wider space. In our explanation we draw on the original concept of spatio-temporal distance by A. Giddens which denotes the stretching of social systems in space and time and which thus relativises the conceptualisation of structure and action. Through a preliminary proposal concerning mobility structuration, we set the framework for solving the dilemma of the relationship between national integration and supranational mobility. Our paper concludes with a Slovenian example where we establish the population's low level of mobility capital. This is a consequence of the rigid socio-territorial organisation and sedentary residential tendencies.
Keywords: družbena mobilnost; Education; Employment; Izobraževanje; Prostorska mobilnost; Prostorska sociologija; Spatial mobility; Spatial sociology; Zaposlovanje